When criminal diversion is a temporary solution: rethinking drug rehabilitation policy in Thailand. Issue 4 (2nd October 2022) - Chokprajakchat, Srisombat; Techagaisiyavanit, Wanaporn; Iyavarakul, Tongyai; Kuanliang, Attapol
ABSTRACT: This article reflects on the need for Thailand to re-evaluate its criminal diversion policy for people who use drugs (PWUD). Although studies have examined the impact of criminalising drug use through social and economic perspectives, the issue of how a punitive legal scheme interplays with PWUD's perceptions of drug use and motivation to seek treatment has not received wide scholarly attention in Thailand. This study's primary objective is to shed light on the adverse effects of legal pressure on motivation among PWUD within Thailand's drug rehabilitation systems to assist in shaping its future policy. The study employed a qualitative methodology: in-depth interviews with 69 participants who received drug treatment under the voluntary and compulsory drug diversionary systems in Thailand, as well as 50 government officials and personnel at the administrative and operational levels within the Thai criminal justice system and rehabilitation agencies. The study found that criminalisation schemes can impede system-level rehabilitation goals by failing to recognise the personal needs of participants, with PWUD entering treatment programs only to avoid criminal prosecution.